A Comparative Analysis of the Diffusion of Mobile Technologies in the Visegrad Four Using an ECM Model - Marcin Salamaga (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: The aim of the paper is to assess the size and rate of diffusion of mobile technologies in the processing industry, and to determine the nature and strength of the impact of investment specialisation (investment attractiveness) and industry export specialisation on this phenomenon in the four Visegrad Group countries.